Yield of community-based tuberculosis targeted testing and treatment in foreign-born populations in the United States: A systematic review. - Mohsen Malekinejad; Andrea Parriott; Amanda P Viitanen; Hacsi Horvath; Suzanne M Marks; James G Kahn (PLoS ONE)
Objective To synthesize outputs and outcomes of community-based tuberculosis targeted testing and treatment (TTT) programs in foreign-born populations (FBP) in the United States (US). Methods We systematically searched five bibliographic databases and other key resources. Two reviewers independently applied eligibility criteria to screen citations and extracted data from included studies. We excluded studies that contained <50% FBP participants or that examined steps only after diagnosis of latent TB infection (LTBI). We stratified studies as majority FBP (50-90%) and predominantly FBP (>90%). We used random-effects meta-analytic models to calculate pooled proportions and 95% confidence intervals (CI) for community-based TTT cascade steps (e.g., recruited, tested and treated), and used them to create two hypothetical cascades for 100 individuals. Results Fifteen studies conducted in 10 US states met inclusion criteria. Studies were heterogeneous in recruitment strategies and mostly recruited participants born in Latin America. Of 100 hypothetical participants (predominantly FBP) reached by community-based TTT, 40.4 (95% CI 28.6 to 50.1) would have valid test results, 15.7 (95% CI 9.9 to 21.8) would test positive, and 3.6 (95% CI 1.4 to 6.0) would complete LTBI treatment. Likewise, of 100 hypothetical participants (majority FBP) reached, 77.9 (95% CI 54.0 to 92.1) would have valid test results, 26.5 (95% CI 18.0 to 33.5) would test positive, and 5.4 (95% CI 2.1 to 9.0) would complete LTBI treatment. Of those with valid test results, pooled proportions of LTBI test positive for predominantly FBP and majority FBP were 38.9% (95% CI 28.6 to 49.8) and 34.3% (95% CI 29.3 to 39.5), respectively. Conclusions We observed high attrition throughout the care cascade in FBP participating in LTBI community-based TTT studies. Few studies included cascade steps prior to LTBI diagnosis, limiting our review findings. Moreover, Asia-born populations in the US are substantially underrepresented in the FBP community-based TTT literature.